UPAYA KEBERHASILAN PEMBERIAN ASI EKSKLUSIF MELALUI EDUKASI DAN PENDAMPINGAN MULAI KEHAMILAN - Noor Azizah; Dyah Ayu Wulandari (Universitas Muhammadiyah Kudus, 2022)
Continuity of care is a continuous service activity starting from pregnancy, childbirth, postpartum, newborn and family planning. These primigravida pregnant women do not yet have knowledge about exclusive breastfeeding so that lactation preparations are carried out when the mother does a pregnancy check. Primigravida by getting knowledge, support and motivation from the midwife as one of the success factors in exclusive breastfeeding. Midwives in providing care are carried out comprehensively. The care provided in pregnancy detects early pregnancy risks, provides education and information according to gestational age, discomfort in the first, second and third trimesters, preparation for lactation. Preparation for lactation is carried out to increase knowledge, provide support, involve husband and family as motivators in exclusive breastfeeding. Assistance to babysitters while the mother is working, namely how to serve expressed breast milk, how to give expressed breast milk to babies. Breastfeeding assistance is carried out not only for mothers but by involving husbands, families and baby caregivers. Expressing breast milk storage is carried out at work, from work to home, to home to refrigerators and freezers and how to serve and how to give.